Using Teaching & Learning Module to Enhance Preschool Children’s Emotional Intelligence: A Preschool Teachers Perception - Aizal Akmal Binti Rohaizad, Nor; Binti Jayus, Rozita; Binti Mohd Kosnin , Azlina; Khan, Aqeel (International Journal of Psychosocial Rehabilitation, 2020)
A preliminary study conducted by the researchers found that preschool teachers in Malaysia are having problems teaching the socio-emotional components due to the lack of specific teaching tools, guidance, and structure. In this study, a teaching module was developed to help preschool teachers in the pedagogy of emotional intelligence (EI) to enhance the preschool children’s EI in Malaysia. This module was developed based on Gagne’s information processing theory, Bandura’s social learning theory, and the zone of proximal development (ZPD) theory by Vygotsky. The module includes ten topics that cover all elements of EI: identifying emotion, understanding emotion, controlling emotion, and using emotion. Activities were designed for each of these elements, and in-service teachers were the ones who taught the children using the module. The effectiveness of this module was examined through an interview among the preschool teachers (experimental group) who were using the module. Results show both preschool teachers in the experimental group are satisfied with the effectiveness of the teaching and learning module to enhance preschool children’s emotional intelligence. It is a significant increase in children’s emotional intelligence in the experimental group. These findings suggest that the module can be a useful tool for preschool teachers to help develop preschool children’s emotional intelligence.